Rights Information Infrastructures and Voluntary Stakeholders Agreements in Digital Library Programmes - Piero Attanasio (JLIS.it, 2010)
Rights management for digital library programs is affected by high transaction costs and this calls for new schemes of collective management. Voluntary Stakeholders Agreements (VSA) is proposed as a solution. However, there is a need to reshape the way of defining the scope of such agreements. In the past, the scope was set by limiting the type of uses licensed in the collective agreement, while other uses, pertaining the primary exploitation of works, remain in the sphere of direct management by the rightholder. In the agreements under discussion in several countries in relation to digital library initiatives, the scope is rather defined through limiting the type of works included in the agreement, while the licensed use is broad, including full making available in the Internet. A key distinction is the commercial status of a work, if it is in-print or out-of-print.Such new VSAs require innovative forms of managing of rights information, i.e. set of metadata referred to rights management. A significant part of transaction costs derives from the search of rightholders, and thus there is a trend to call for reducing or even abolishing the need for this search. However, the identification of the right status (public domain vs. in-copyright) and the commercial status (in print vs. out of print) requires a title by title management of information, which is inevitable because of the characteristics of the emerging VSAs. The proper rightholder search cost should be assessed as an additional cost to something that is in the nature of the agreements. The paper tries to set the terms and conditions to achieve this assessment, and to figure out practical solutions to the problem.